Recent Advances in Multifunctional Hydrogels for the Treatment of Osteomyelitis - Xin, Weiwei; Gao, Yingjian; Yue, Bing (Frontiers in Bioengineering and Biotechnology, 2022)
Osteomyelitis (OM), a devastating disease caused by microbial infection of bones, remains a major challenge for orthopedic surgeons. Conventional approaches for prevention and treatment of OM are unsatisfactory. Various alternative strategies have been proposed, among which, hydrogel-based strategies have demonstrated potential due to their unique properties, including loadable, implantable, injectable, printable, degradable, and responsive to stimuli. Several protocols, including different hydrogel designs, selection of antimicrobial agent, co-administration of bone morphogenetic protein 2(BMP 2), and nanoparticles, have been shown to improve the biological properties, including antimicrobial effects, osteo-induction, and controlled drug delivery. In this review, we describe the current and future directions for designing hydrogels and their applications to improve the biological response to OM in vivo.